Neurobehavioural Changes and not Structural Changes Occur in Rat Fed with Cassava Products (Fufu, Garri and Tapioca Diet) - , Lekpa K. David; , Eric Umeakaelu; , Chinagorum Ibeachu (Archives of Current Research International, 2021)
The ability of cassava products (fufu, garri and tapioca) to produce behavioral and structural changes in the brain of adult rats was examined. Forty adult male rats (N=40) were used for this study and the experiment was divided into two phases (N=20 each).Rat were trained in a Reach-To-Grasp Task for 6 weeks and Quantitative assessments using a reaching movement scale and reach-to-grasp success rate were carried out to determine baseline values. After which administration of the various cassava products was done. The 1st phase had the rats trained to perform the reach to grasp experiment before been fed with various cassava diet. In this phase the animals performed significantly worse than the controls when determining the average success rate in a reach-to-grasp experiment (baseline=72.6%, fufu diet= 30%, garri diet =47%, tapioca diet =59%). The 2nd phase had the rats trained simultaneously as they were being fed withvarious cassava diet. In this phase the animals also performed significantly worse than the controls when determining the average success rate in a reach-to-grasp experiment (fufu diet= 37.5%, garri diet =46.5%, tapioca diet =56.5%). The various movement of the rat was assessed using Tracker software (Video Analysis and Modeling tool, version 5.1.2) and the movement pattens were determined. The animals fed with Fufu shows the worst movement pattern indicating aiming impairment which may be as a result of structural changes in the m1 region of the cerebral cortex. The data obtained were analysed using ANOVA and there was significant difference (p < 0.05) in the movement pattern. Histological observation showed no neuropathological changes in the motor cortex. The rats fed with cassava diets shows no observable changes in the structures and sizes of the neurons as compared with the control. Cassava products (Fufu, Garri and Tapioca) have been demonstrated to cause neurobehavioural and mild structural changes in the M1 region of the cerebral cortex.